Comprehensive pinch-exergy analyzes of the NGL recovery process - Fakhrodin Jovijari; Abbas kosarineia; Mehdi Mehrpooya; Nader Nabhani (Gas Processing Journal, 2022)
Energy quality is a very important criterion, which affects the economic growth of that country. In this study, a real-life case study Natural Gas Liquids plant 800, from National Iranian South Oil Company located in the southwest of Iran was considered by conventional exergy analysis, advanced exergy analysis, combined pinch and exergy analysis, and combined pinch and advanced exergy analysis methods. The results of conventional exergy analysis illustrate that the highest amount of exergy destruction belongs to compressors and heat exchangers with 510 and 629 kW respectively. The advanced exergy analysis suggested that the exergy destruction of the heat exchanger and compressor and will reduce by modifying the performance of these components. However, according to this analysis, for (E-101) heat exchanger despite having the highest rate of exergy destruction, is not in the priority of modification due to its low level of avoidable exergy destruction. Also, the avoidable, endogenous part of exergy destruction of the compressor (K103) and heat exchanger (E-102) will reduce by improving the performance of these components. In the following, and by using the combined Pinch and advanced exergy analysis diagram, it was possible to display simultaneously the energy consumptions rate and the unavoidable exergy destruction of the heat exchanging network. According to this graphical analysis, the plant's minimum hot and cold required utilities are equal to 411 and 10,211 kW, respectively for ΔTmin of 10.645 °C. And heat exchanger E-102 has more priorities of improvement compared to other heat exchangers.